Ejection fraction basal strain ratio (EFBSR), a new accurate echocardiographic deformation parameter to screen cardiac amyloidosis among hypertrophic cardiopathies. (14th October 2021) - Rique, A; Martel, H; Piazzai, C; Mancini, J; Gravier, R; Arregle, F; Dernys, A; Gardenat, A; Casalta, A C; Renard, S; Hubert, S; N'guyen, K; et al.
Abstract: Background: Early diagnosis of cardiac amyloidosis (CA) is challenging. Several echocardiographic (echo) parameters have been proposed to differentiate CA from hypertrophic cardiomyopathy (HCM), but their respective value is debated. CA is known to be characterized by a more severe decline in longitudinal deformation parameters as compared with radial function parameters (LVEF). This characteristic justified the use of the ejection fraction strain ratio (EFSR) in these patients. However, since longitudinal dysfunction usually predominates in basal segments (apical sparing), we postulated that a new parameter focusing on LVEF and basal LV deformation (EFBSR: ejection fraction basal strain ratio) will even better discriminate patients with CA from HCM than EFSR and other echo or strain parameters. Purpose: To compare the accuracy of deformation-based echocardiographic parameters for detecting CA in a population with different causes of LV hypertrophy. Methods and results: We included 237 subjects, of which 89 patients with CA (77±10.7 years, 72% male, EF: 56.2±12.8%, and mean interventricular septum: 18.3±3.5 mm), 137 patients with hypertrophic cardiomyopathies (HCM), 52 patients with severe aortic stenosis with myocardial remodeling, 20 patients with arterial hypertension, and 20 control patients. Conventional echocardiographic parameters and strain-derived ratios (Relative apical sparing (RELAPS), Ejection Fraction Strain Ratio (EFSR) and EFBSR) were analyzed. EFBSR and RELAPS presented with the best performance to discriminate CA from other causes of hypertrophy (Area Under the Curve (AUC): 0.880; 95% CI: 0.830–0.929 and 0.903; 95% CI: 0.863–0.943 respectively) (p-value=0.3). In our study, among all the parameters, RELAPS had the best specificity (89.8% vs 88.3% for EFBSR), whereas EFBSR had the best sensitivity (78.7% vs 76.4% for RELAPS). EFBSR ranged from 35.25 to 1.83 and the cutoff value to differentiate CA from other hypertrophic cardiopathy was an EFBSR >7.75. Conclusions: Our study demonstrates that in patients with LV hypertrophy, a new deformation parameter, the ejection fraction basal strain ratio (EFBSR) can accurately differentiate CA from other causes of myocardial thickening and can be used in routine practice for screening. Funding Acknowledgement: Type of funding sources: None.